N6-Methylandenosine-Related lncRNA Signature Is a Novel Biomarkers of Prognosis and Immune Response in Colon Adenocarcinoma Patients - Zhang, Peiling; Liu, Guolong; Lu, Lin (Frontiers in Cell and Developmental Biology, 2021)
Background: Colon adenocarcinoma (COAD) is the most common type of colon cancer. But to date, the prognostic values of m6A RNA methylation-related long non-coding RNAs (lncRNAs) in COAD are largely unknown. Material and methods: The m6A-related lncRNAs were identified from The Cancer Genome Atlas (TCGA) dataset. Univariate and multivariate Cox regression analyses were performed to explore the prognostic m6A-related lncRNAs. Consistent clustering analysis was performed to classify the COAD patients into different subgroups based on the expression of m6A-related lncRNAs. The potential biological functions, as well as differences in the stemness index and tumor immune microenvironment between different subgroups, were analyzed. The prognostic m6A-related lncRNAs were used to establish a m6A-related lncRNA risk model to predict prognosis and survival status. Results: We identified 31 m6A-associated lncRNAs with prognostic values from the TCGA dataset. Based on the expression of prognostic m6A-associated lncRNAs, TCGA-COAD patients were classified into three clusters using consistent clustering analysis. There was a low correlation of the tumor stemness between the three clusters, but a significant correlation with tumor immune microenvironment, as well as the tumor mutational load. Thirty one prognostic-related m6A-associated lncRNAs were used to construct a risk model, which was further determined by survival analysis, ROC curve, univariate and multifactor Cox analysis. The m6A-related risk model demonstrated good performance in predicting prognosis and survival status. The model-based high-risk group exhibited poorer overall survival (OS) compared to the low-risk group. Conclusion: In this study, we constructed a risk model which was consisted of 31 m6A-related lncRNAs with independent prognostic values in COAD. Our study showed the critical roles of these 31 m6A-related lncRNAs in the tumor immune microenvironment, which indicating the prospect of informing the prognostic stratification and the development of immunotherapeutic strategies for COAD patients.